Evaluation on the performance and wear of blades in a small-sized high-density polyethylene shredder - A. B. Jalisa; J. H. Wong; W. M. J. Karen1; Willey Liew Yun Hsien; Chua Bih Lii, Bih Lii; Nancy Julius Siambun; Melvin Gan Jet Hong (Wiley Online Library, 2024)
In this study, a small-sized shredder machine equipped with spiral oriented double-edged rotating and fixed blades was utilized to shred high-density polyethylene (HDPE) waste. The performance of the shredder machine was determined based on the recycling and shredding efficiency, the percentage of retention, and the wear of its rotating and fixed blades. The wear of the blades was examined using an optical microscope, a scanning electron microscope, an energy dispersive x-ray, and an x-ray diffraction. High recycling (~95%– 98%) and shredding (~66%–70%) efficiency, and low percentage of retention (~1.2%–4.1%) indicated a reliable performance of the shredder machine. The rotating blade exhibited higher wear at the back end, compared to the front end for the fixed blade. The wear of the blades was due to scratching and edge chipping. Formation of iron oxides during shredding did not cause significant changes in the hardness of the blades. Based on the evaluation, cost-effective and time saving maintenance of the shredder blades could be achieved by gradual maintenance starting from the blade exhibited high wear